#celiacdisease: The Use of Instagram in Contending with Chronic Illness. Issue 1 (2nd January 2020) - Meleo-Erwin, Zoe; Basch, Corey H.; Fera, Joseph; Smith, Bonnie
Abstract: There is a dearth of information on the use of Instagram by celiac disease patients. To address this gap, a convenience sample of 150 posts was first coded as personal stories, support systems, and management of celiac disease and then coded using a number of additional deductive sub-category codes. Descriptive statistics were then calculated. The mean number of likes was 98.56 with a standard deviation of 348.4. In terms of major categories, the majority of the posts fell under "personal stories" (52.67%). Of the sub-category codes or characteristics, only four were statistically significant: lists ingredients/recipes, stress or hardship about being gluten-free, picture of food, and place to buy food mentioned. This study finds that Instagram posters primarily use the social media site to share personal stories.